Towards high-energy storage density in thermal energy storage systems - Yang, Wu Xi (2016)
Thermal energy storage is an increasingly popular research area due to the rise in energy consumption patterns around the world. There is a variety of storage systems available commercially like sensible heat storage systems, latent heat storage systems and last but not least, thermo-chemical heat storage systems, each with different advantages and disadvantages that come along with them. This project aims to study the introduction of forced convection and thermal conductivity enhancement in phase change materials (PCMs) and the effects that these parameters would have on the charging rate, which is also known as the time taken to fully melt for a given amount of material. The PCM chosen for this project is technical grade paraffin wax. Paraffin wax was chosen for its high heat storage capacity and non-reactive nature. Its melting temperature also fulfilled the value required for the targeted area of application, which was low grade heat recovery. Magnetic stirring would be the forced convection mechanism of choice for this project, and the addition of graphite powder to the PCM would be the form of thermal conductivity enhancement used. A CFD model would then be developed for the baseline experiment, and be matched with actual experimental results to see if the model is suitable for running simulations. Three experimental phases were designed and conducted throughout the course of this project, with an initial proof-of-concept phase, a modified and refined phase and a final experimental phase. A control experiment was established as a baseline for comparisons with experimental runs with modifications. Analysis of variance (ANOVA) was used to determine if the factors had significant effect on the response, which was the charging rate, or the total time taken for the PCM to melt. However, due to inconclusive values obtained from ANOVA, direct comparison of timings was conducted and results have shown that magnetic stirring had a bigger effect on the charge rate than the addition of graphite powder.